Persepsi Kesatuan Tindak Tutur Memerintah dalam Bahasa Indonesia - Manaf, Ngusman Abdul (UI Scholars Hub, 2002)
This study discusses the relationship between indirect speech act and politeness in directive speech act. To get the data, questioners with personal information of respondents and nine directive speech acts which must be assessed by these Indonesian speakers in Jakarta are employed. The analysis shows that there is a positive correlation between the indirectness of a directive speech act and the degree of politeness. The more indirect a directive speech act, the more polite it is. Nevertheless, the correlation is not absolute. There are other parameters that determine the degree of politeness such as intonation, choice of words, and cultural values of the speakers.